1991
DOI: 10.1007/bf00571734
|View full text |Cite
|
Sign up to set email alerts
|

A defective proviral DNA with a 2.6-kb deletion of human immunodeficiency virus type 1 (HIV-1) in a persistently HIV-1 infected cell clone

Abstract: A cell line (H2-5) producing defective doughnut-shaped particles of human immunodeficiency virus type I (HIV-1) was found to contain proviral DNA with a large deletion of 2558 bases, corresponding to the 3' half of pol gene, the vif and vpr genes, and the 5' terminal of the tat gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…For a probe, HIV-1 32p-labeled HindIII DNA fragments at nucleotides 531 to 9606 containing almost the entire HIV-1 genome ofpNL 432 were prepared as described previously [11].…”
Section: Hiv-1 Dna Structural Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…For a probe, HIV-1 32p-labeled HindIII DNA fragments at nucleotides 531 to 9606 containing almost the entire HIV-1 genome ofpNL 432 were prepared as described previously [11].…”
Section: Hiv-1 Dna Structural Analysismentioning
confidence: 99%
“…Thus, it is important to determine which HIV-t gene(s) are required for MT-4 cell death. We previously reported that HIV-1 D N A structural analyses of cell clones isolated from MT-4/HIV-1 by Southern blotting revealed deletion at different sites of the proviral HIV-1 DNA, and one cell clone producing defective doughnut-shaped particles (designated as H 2-5) contained proviral D N A with a large deletion of 2558 bases, corresponding to the 3' half of the pol gene, the entire v/f and vpr genes, and the 5' terminal of the tat gene [11]. Here we report the cell killing capacity of HIV-1 vif, vpr, vpu, and n e f m u t a n t viruses in the MT-4 cell system.…”
Section: Introductionmentioning
confidence: 99%
“…DNA and poly(A)* RNA fractions were prepared from cells as previously described (Chomczynski & Sacchi, 1987;Imai et al, 1991). Southern and Northern blot hybridizations were carried out as described previously .…”
Section: Immunofluorescence (If) Testmentioning
confidence: 99%
“…Thus, clone B7 cells constitutively produce high levels of homogeneous, replication-defective VLP (SIVsmB7). Others laboratories have established cell lines harboring defective proviruses [13,14]. B7 cells are also clonal in nature, and produce non-infectious particles that have been shown to be immunogenic.…”
mentioning
confidence: 97%
“…However, the presence of a single, defective proviral genome in the B7 chromosomes strengthens the hypothesis of the faulty reverse transcription. Of interest, chronically infected cells producing Pol-deleted/mutated HIV have been reported by others [13,14]. Nevertheless, the mechanisms by which a Pol/Vpr-defective genome (such as SIVsmB7 DNA) can integrate into the host cell genome have yet to be elucidated.…”
mentioning
confidence: 98%